#### Answer

-2

#### Work Step by Step

$-\frac{\sqrt -64}{\sqrt -16}=-\frac{i\sqrt 64}{i\sqrt 16}=-\frac{i}{i}\times\frac{\sqrt 64}{\sqrt 16}=-1\times\sqrt \frac{64}{16}=-1\times\sqrt 4=-1\times2=-2$
We know that $\sqrt -1=i$, because $i^{2}=-1$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.